Experiences with maternal and perinatal death reviews in the UK—the MBRRACE‐UK programme. (September 2014) - Kurinczuk, JJ; Draper, ES; Field, DJ; Bevan, C; Brocklehurst, P; Gray, R; Kenyon, S; Manktelow, BN; Neilson, JP; Redshaw, M; Scott, J; Shakespeare, J; et al.
Abstract : Established in 1952, the programme of surveillance and Confidential Enquiries into Maternal Deaths in the UK is the longest running such programme worldwide. Although more recently instituted, surveillance and confidential enquiries into perinatal deaths are also now well established nationally. Recent changes to funding and commissioning of the Enquiries have enabled both a reinvigoration of the processes and improvements to the methodology with an increased frequency of future reporting. Close engagement with stakeholders and a regulator requirement for doctors to participate have both supported the impetus for involvement of all professionals leading to greater potential for improved quality of care for women and babies.